2013
DOI: 10.3138/cjccj.2011-e-46
|View full text |Cite
|
Sign up to set email alerts
|

Taming Disorderly People One Ticket at a Time: The Penalization of Homelessness in Ontario and British Columbia

Abstract: In the last two decades, provincial and local governments in Canada took a new series of measures to regulate urban disorder and control how public spaces were used by homeless people. Ontario became the first province to adopt new legislation with the passage of the Safe Streets Act, 1999. British Columbia soon followed the same path and enacted its own Safe Streets Act in 2004. This article focuses on the enforcement of the Safe Streets Act in Ontario and BC. Using quantitative data on tickets delivered to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 15 publications
0
34
0
3
Order By: Relevance
“…[45][46][47][48][49][50] Our study documented similar instances of discriminatory surveillance and harassment of PWUD by security guards. Mirroring findings among traditional police forces, our study identified that prejudicial conduct was often racialized and gendered, findings that are also consistent with community legal research on security guard practices in Vancouver.…”
Section: Discussionmentioning
confidence: 55%
“…[45][46][47][48][49][50] Our study documented similar instances of discriminatory surveillance and harassment of PWUD by security guards. Mirroring findings among traditional police forces, our study identified that prejudicial conduct was often racialized and gendered, findings that are also consistent with community legal research on security guard practices in Vancouver.…”
Section: Discussionmentioning
confidence: 55%
“…By issuing fines and jail time, and by deepening social and economic marginalization, these practices foster the very conditions that contribute to homelessness. Antihomeless ordinances, such as those examined in the current study, can only be viewed as "successful" if we are forthright about their social and political purpose-to sanitize public space, enforce spatial boundaries of deservingness, and deepen the institutional stigmatization of poverty in its many forms (Aulette & Aulette, 1987;Bancroft, 2012;Chesnay et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The "erasure" of people who are homeless from community settings is supported by ordinances that prohibit life-sustaining activities such as sleeping/camping, eating, sitting, and/or asking for money/resources in public spaces (National Law Center on Homelessness and Poverty, 2011;NLCHP and NCH, 2009). Antipanhandling and antiloitering laws, sleeping bans, and zoning regulations are part of a system of policies that criminalize homelessness, with financial and criminal penalties issued for sleeping on park benches and in cars, resting in public space for longer than a specified amount of time, or standing within a certain distance of businesses (Aguirre & Brooks, 2001;Amster, 2003;Blasi, 2007;Chesnay, Bellot, & Sylvestre, 2013;NLCHP, 2011;NLCHP and NCH, 2009;Wachholz, 2005a). Collectively, these policies enforce spatial exclusion by making public areas "off limits" to people who are homeless and severely limit freedom of movement.…”
Section: Criminalizing Homelessness: Antihomeless Ordinances and Spatmentioning
confidence: 98%
“…En fait, selon la littérature, se cacheraient derrière ces pratiques discriminatoires des intérêts économiques, politiques et institutionnels particuliers (Sylvestre, et collab., 2011). Des préoccupations liées au tourisme, à l'industrie et à la revitalisation ainsi que le phénomène de gentrification auraient exacerbé les conflits liés à l'occupation des espaces publics (Chesnay, Bellot et Sylvestre, 2013;Colombo et Larouche, 2007;Morin, Parazelli et Benali, 2008;O'Grady, Gaetz et Buccieri, 2011). C'est pourquoi nous avons demandé aux agentes et agents professionnels participant aux entretiens collectifs de nous décrire la spécificité du profilage social tel qu'il se dessine dans la ville de Gatineau.…”
Section: Les Circonstances : Le Contexte Du Profilage Social à Gatineauunclassified